Sustainable Reinforcement Methods for Brick Masonry Walls: An Experimental and Finite Element Analysis Approach - Tahir Mehmood; Muhammad Amer Abid; Burachat Chatveera; Gritsada Sua-Iam; Panumas Saingam; Ali Ejaz; Qudeer Hussain; Panuwat Joyklad; Suniti Suparp (Buildings, 2025)
This study investigates the enhancement of axial and shear strength in brick masonry walls reinforced with steel and fiberglass meshes. The novelty of this study lies in its thorough evaluation of various reinforcement types and their influence on both axial and shear strength, offering valuable insights to enhance the performance of brick masonry structures. By using steel and fiberglass meshes for reinforcement, the study promotes the use of durable materials that can extend the lifespan of brick masonry structures, reducing the need for frequent repairs and replacements. The findings reveal that double-layer steel mesh delivers the highest strength, effectively reducing brittleness and improving deformation capacity in both single- and double-brick walls. Specifically, single-brick walls exhibited increases in compressive strength of 38.8% with single-layer steel mesh, 31.2% with fiberglass mesh, and 19.7% with plaster. In contrast, double-brick walls showed enhancements of 73.6% with double-layer steel mesh and 43.5% with fiberglass mesh. For shear strength, single-brick walls improved by 115.1% with single-layer steel mesh, 91.3% with fiberglass mesh, and 42.1% with plaster, while double-brick walls experienced increases of 162.7% with double-layer steel mesh and 132.5% with fiberglass mesh. Additionally, Abaqus modeling under axial and diagonal compression closely matched experimental results, revealing less than a 10% discrepancy across all reinforcement types.